A bacterial strain of Pseudomonas aeruginosa B0406 pathogen opportunistic, produce a biosurfactant with tolerance to changes of pH, salinity and temperature. (February 2020) - Somoza-Coutiño, Gilberto; Wong-Villarreal, Arnoldo; Blanco-González, Cristina; Pérez-Sariñana, Bianca; Mora-Herrera, Martha; Mora-Herrera, Silvia Ivonne; Rivas-Caceres, Raymundo Rene; de la Portilla-López, Nadia; Lugo, Jorge; Vaca-Paulín, Rocío; del Águila, Pedro; Yañez-Ocampo, Gustavo
Abstract: A bacterial strain of Pseudomonas aeruginosa B0406 catalogued as pathogen opportunistic was capable to grow with waste cooking oil as only carbon source and produce a biosurfactant. Stability to pH (from 2 to 12), salinity (% NaCl from 0 to 20%) and temperature (from −20 °C up to 120 °C), of biosurfactants was evaluated using a response surface methodology. Biosurfactants reduced surface tension from 50 to 29 ± 1.0 mN/m. Pseudomonas aeruginosa B0406 showed a high biosurfactant yield 4.17 g/L ± 0.38. Biosurfactants stability applying a response surface methodology was observed with combining effect of pH, salinity and temperature. The three factors combined do not affect surface tension of biosurfactants produced by Pseudomonas aeruginosa B0406. Therefore, this biosurfactants are of interest for medical, cosmetic even environmental applications. Graphical abstract: Image 1 Highlights: Promising surface tension is produced by pathogen opportunistic P. aeruginosa B0406. Biosurfactant produced by P. aeruginosa B0406 exhibited environmental stability. Surface methodology was useful for evaluating surface tension in extreme conditions. Temperature, pH and salinity changes, do not affect surface tension of BS B0406.